Vampire Bat Salivary Plasminogen Activator Evokes Minimal Bleeding Relative to Tissue-Type Plasminogen Activator as Assessed by a Rabbit Cuticle Bleeding Time Model - Mellott, Michael J; Ramjit, Denise R; Stabilito, Inez I; Hare, Timothy R; Senderak, Edith T; Lynch, Joseph J, Jr; Gardell, Stephen J (Thrombosis and Haemostasis, 1995)
Cuticle bleeding time (CBT) measurements in anesthetized rabbits were performed to assess the potential bleeding risks which may accompany the administration of tissue-type plasminogen activator (tPA) or vampire bat salivary plasminogen activator (BatPA). The dose of BatPA or tPA used in this study, 42 nmol/kg, was previously shown to be efficacious using a rabbit femoral artery thrombosis model (Gardell et al, Circulation 84:244, 1991). CBT was determined by severing the apex of the nail cuticle and monitoring the time to cessation of blood flow. CBT was minimally elevated (1.6-fold, p<NS) following bolus intravenous administration of BatPA; in contrast, bolus intravenous administration of tPA dramatically elevated CBT (6.2-fold, p<0.05). Rabbits treated with tPA, but not BatPA, displayed profound activation of systemic plasminogen and consequent degradation of Factor VIII and fibrinogen. Elevations in CBT after the administration of tPA were reversed by the replenishment of plasma Factor VIII activity to 40% of control, but were unaffected by complete replenishment of plasma fibrinogen. The results of this study suggest that the administration of BatPA, at a dose that promotes thrombolysis, may evoke a minimal bleeding risk, relative to an equi-efficacious dose of tPA. In addition, the tPA-provoked proteolytic consumption of Factor VIII may be a key contributor to the heightened bleeding risk.